Extração do óleo de favela (Cnidoscolus quercifolius) sob diferentes métodos e sua potencialidade como biocombustível - Allein, Fabiola (2020)
The favela (Cnidoscolus quercifolius) is a plant native to the Brazilian Caatinga, with significant economic and environmental potential. It stands out for being a plant highly resistant to drought and with high nutritional content, presenting several applications, such as in animal feed (goats, cattle and sheep), medicinal, and in the production of biofuels. Although the favela has seeds rich in oil, being considered a potential alternative for the production of edible oil, little information is found in the literature about its extraction and characterization. In this context, this study aimed to study the methods of extracting favela oil for future applications in the synthesis of biodiesel. For the study of the extraction of favela oil (Cnidoscolus quercifolius) different methods were used, such as classic extraction by mechanical pressing and non-classical methods, such as extraction with Goldfish apparatus (continuous lipid extractor) and with supercritical fluid (CO2) pure, with the addition of co-solvent ethanol and ethyl acetate in the extraction process. The extraction method, in which a higher oil yield was obtained, was the lipid extractor by Goldfish. In this extraction and with the ethanol solvent, a higher yield (40.17%) was obtained compared to the other extraction methods. Regarding the composition of fatty acids and thermal stability, there was no significant difference as to the method and solvent used. Regarding the composition of fatty acids in oil from the favela, linoleic (C18: 2 n6) predominated with an average of 43.33%, followed by oleic (C18: 1 n9) with an average of 21.34% for all analyzed samples.The analyzes of Thermogravimetry (TG) and Differential Exploratory Calorimetry (DSC) showed that the samples had high thermal stability, which degraded at temperatures above 350ºC on average. The content of tocopherols and phytosterols was higher for the oil extracted by the mechanical press, in relation to the average of the compounds obtained in the classic extraction; β-tocopherol was the predominant compound (209.90 mg 100 g-1), followed by β-sitoesterol (160.9 mg 100g-1); γ-tocopherol (43.02 mg 100g-1) and δ-tocopherol (31.47 mg 100g-1); respectively. In general, Cnidoscolus quericifolius proved to be an interesting raw material option for the production of biodiesel.